2011
DOI: 10.1177/0021886310395514
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Positive Practices on Organizational Effectiveness

Abstract: Emphasis on positivity in organizations in increasing, but the importance and credibility of a positive approach to change-exemplified by positive organizational scholarshipremains controversial. More empirical evidence is needed showing that positive practices in organizations produce desirable changes in organizational effectiveness. Two studies-one in financial services and one in the health care industry-are reported, which investigate the link between positive practices and indicators of organizational ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
246
0
22

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 241 publications
(308 citation statements)
references
References 91 publications
10
246
0
22
Order By: Relevance
“…Two additional studies specifically investigated the extent to which leadership virtuousness produces these performance improvements rather than having higher performance lead to virtuousness on the part of leaders (Cameron et al 2011). One study examined 40 financial service organizations, and the other examined 30 health care organizations over multiple years to discover what happened to performance when virtuousness scores increased or decreased.…”
Section: Virtuousness and Positive Organizational Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Two additional studies specifically investigated the extent to which leadership virtuousness produces these performance improvements rather than having higher performance lead to virtuousness on the part of leaders (Cameron et al 2011). One study examined 40 financial service organizations, and the other examined 30 health care organizations over multiple years to discover what happened to performance when virtuousness scores increased or decreased.…”
Section: Virtuousness and Positive Organizational Outcomesmentioning
confidence: 99%
“…Of course, what is considered good is often controversial, 2 but one term that connotes universal standards of rightness, correctness, and goodness is the concept of virtuousness (Cameron and Winn 2012;Cameron et al 2011). This concept is a universally accepted standard for the best of the human condition (Comte-Sponville 2001; Dutton and Sonenshein 2007;Peterson and Seligman 2004).…”
mentioning
confidence: 99%
“…Market culture emphasizes rationalized actions culminating into efficient and productive planning of achieving organizational goal settings. Market culture orientation was found to have influenced organizational commitment through its impact on behaviour pattern of employees in diverse organizations (Yildirim, Acaray and Candan, 2016).Individuals are expected to understand the corporate values and expectations of the organization and the relevance of each and every role, thereby inspiring and motivating employees' commitment in achieving organizational goals (Cameron et al, 2011) …”
Section: The Market Culturementioning
confidence: 99%
“…Their research program has shown associations of PSC with levels of workplace bullying and post-traumatic stress (Bond et al, 2010), harassment, psychological distress and low levels of employee engagement (Law et al, 2011), emotional exhaustion and low levels of job satisfaction (Dollard and Bakker, 2010). POSITIVE ORGANIZATIONS Cameron et al (2011) carried out studies in two sectors, financial services and healthcare, and found that positive organizational practices (e.g., caring, compassionate support, forgiveness, inspiration, meaning, respect, integrity and gratitude) were associated with higher levels of employee and client satisfaction and lower turnover and higher levels of organizational performance, and that increases in positive practices over time were associated with increased organizational performance over time. Quinn (2015), building on emerging findings from positive organizational behaviour, made the case for 'positive organizations'.…”
Section: The Psychosocial Safety Climatementioning
confidence: 99%